2018
DOI: 10.1002/jat.3720
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic acid supplementation ameliorates testicular hormonal signaling, sperm production and oxidative stress in male rats exposed to rosuvastatin during pre‐puberty

Abstract: Dyslipidemias are occurring earlier in the population due to the augmentation of obesity. Rosuvastatin reduces cholesterol and triglycerides; however, previous studies have shown that it may affect male reproduction. Ascorbic acid (AA), an antioxidant compound, plays a protective role in the male reproductive system. This study aimed to evaluate whether pre‐pubertal exposure to rosuvastatin may impair testicular structure and antioxidant status in male rats and if supplementation with AA may alleviate these da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 70 publications
1
3
0
Order By: Relevance
“…Under normal physiological conditions, ROS produced in the body can be dynamically balanced by the anti-oxidative stress defense system, including SOD, CAT, and GSH (Cannarella et al, 2019). Studies have found that obesity can affect the body's oxidative stress levels through a variety of ways, including energy metabolism and the mitochondrial electron transport chain, leading to increased ROS and male infertility (Leite et al, 2019). In the present study, compared to the control mice, expression levels of GSH and SOD were significantly decreased, while expression levels of MDA were significantly increased in the testis tissues of HFD-induced obese mice.…”
Section: Discussionsupporting
confidence: 40%
“…Under normal physiological conditions, ROS produced in the body can be dynamically balanced by the anti-oxidative stress defense system, including SOD, CAT, and GSH (Cannarella et al, 2019). Studies have found that obesity can affect the body's oxidative stress levels through a variety of ways, including energy metabolism and the mitochondrial electron transport chain, leading to increased ROS and male infertility (Leite et al, 2019). In the present study, compared to the control mice, expression levels of GSH and SOD were significantly decreased, while expression levels of MDA were significantly increased in the testis tissues of HFD-induced obese mice.…”
Section: Discussionsupporting
confidence: 40%
“…The rosuvastatin doses chosen for this study are based on the lowest and highest doses applied in human therapy for children ( Leite et al, 2018a , Leite et al, 2019b , Leite et al, 2018c ), adapted for rodents considering their body surface area, as proposed for Reagan-Shaw et al ( Reagan‐Shaw et al, 2008 ).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies investigating peri -pubertal rosuvastatin exposure in a rodent experimental model revealed that this drug leads to reproductive impairments in male rats. Rosuvastatin can delay pubertal development, reduce sperm quality, impair spermatogenesis, and alter hormonal signaling ( Leite et al, 2014 , Leite et al, 2018a , Leite et al, 2019b ). Also, rosuvastatin exposure in male rats might affect reproductive function in an intergenerational manner, by damaging ovarian and uterine histophysiology of female offspring ( Leite et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Its research focuses on pre-pubertal. Studies have shown that rosuvastatin reduces sperm quality, increases oxidative stress, increases DNA damage, damages testicular tissue, causes pathological changes in testicular and epididymal tissue, reduces testosterone levels, and damages the distribution of steroid receptors ( Leite et al, 2019 ; Leite et al, 2017 ; Leite et al, 2018 ). Additionally, research on antihypertensive drugs has shown that irbesartan and carvedilol play a protective role in testicular injury caused by diseases through anti-inflammatory, antioxidant and anti-apoptotic effects ( Abu-Risha et al, 2022 ; Eid et al, 2016 ; Eid et al, 2019 ; Kabel et al, 2020 ; Ramzy et al, 2014 ).…”
Section: Main Textmentioning
confidence: 99%